Extensive Icthyosis Uteri with in situ Carcinoma - Jyoti Kiran Kudrimoti; Almas Sahir Chopdar; Shaila Chandrakant Puranik (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
A rare disorder known as icthyosis uteri causes the endometrium’s whole surface to be replaced with stratified squamous epithelium. Due to its rarity, two cases of icthyosis uteri have been reported. The first case was a 70-year-old woman who had lower abdominal pain and white PV (per vaginal) discharge for three months prior. The second case included a 70-year-old woman who had been experiencing breathlessness and PV (per vaginal) spotting for a year. In the first case, a gross examination of the uterine cavity revealed an uneven and rough endometrial surface, but in the second case, the endometrium was atrophic. In both cases, endometrial glands were completely replaced by stratified squamous epithelium with in situ carcinoma or severe dysplasia, according to endometrium microscopy. Cervix in both the cases showed severe dysplasia or CIN (cervical intra epithelial neoplasia) III.